Exploration of Cascade Cyclizations Terminated By Tandem Aromatic Substitution: Total Synthesis of (+)-Schweinfurthin A - Topczewski, Joseph J. (2011)
The termination of epoxide-initiated cascade cyclizations with a range of “protected” phenols is described. When the protecting group can be lost as a stabilized electrophile, the cascade process continues beyond ring closure to afford products which have undergone a tandem electrophilic aromatic substitution. A number of groups have proven viable in this process and the regiochemistry of their substitution reactions has been studied. Application of this methodology in the first total synthesis of (+)-schweinfurthin A, a potent anti-proliferative agent, has been achieved.